1990
DOI: 10.1177/030089169007600417
|View full text |Cite
|
Sign up to set email alerts
|

The Management of Inoperable Gastrointestinal Obstruction in Terminal Cancer Patients

Abstract: The aim of the study was to assess vomit and pain control in terminal cancer patients with inoperable gastrointestinal obstruction, using a pharmacologic symptomatic treatment which prevents recourse to nasogastric tube placement and intravenous hydration, in hospital and home care settings. Twenty-two symptomatic patients, who were judged as inoperable, were treated with a pharmacologic association of morphine hydrochloride and scopolamine butylbromide as analgesics and haloperidol as an antiemetic. The drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(43 citation statements)
references
References 20 publications
0
42
0
1
Order By: Relevance
“…The current mechanistic approach to the management of nausea in advanced cancer which is based on the neuropharmacology of the putative "emetic pathway" should be the basis for choosing first-line antiemetic drugs (grade of recommendation: B [8,10] [8,9,17,37]). 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current mechanistic approach to the management of nausea in advanced cancer which is based on the neuropharmacology of the putative "emetic pathway" should be the basis for choosing first-line antiemetic drugs (grade of recommendation: B [8,10] [8,9,17,37]). 5.…”
Section: Discussionmentioning
confidence: 99%
“…A second electronic search for studies specifically about nausea in inoperable bowel obstruction revealed 77 publications of which 12 (16%) appeared relevant. Of these 12, 5 met the inclusion criteria consisting of one meta-analysis [33], the two RCT considered in the metaanalysis [34,35] and two case series [36,37]. Hand searching identified another case series missed by the electronic search [38].…”
Section: Trial Flowmentioning
confidence: 99%
“…Even intravenous hydration should be limited to meeting specific goals rather than correcting inadequate fluid intake. Differences in the mean survival from the appearance of bowel obstruction have been reported (ranging from 17 days to 3.7 months) in advanced cancer patients treated by medical management [5,46,48,70], depending on the different settings of the study and methodology of diagnosis. Clinical experience with the management of home PN in 13 cancer patients with bowel obstruction has recently been reported [45].…”
Section: Advanced Cancer and Bowel Obstructionmentioning
confidence: 99%
“…Unfortunately poor candidates for PN are evident retrospectively. Different mean survival times from the appearance of the bowel obstruction have been reported (ranging from 17 days to 3.7 months) in advanced cancer patients treated by medical management [6,24,43,64]. This wide variation may be due to the different settings of the study, the different combinations of drugs used, criteria of admission and method of diagnosis, as well as the patient population.…”
Section: Nutrition In Case Of Bowel Obstructionmentioning
confidence: 99%